Lettere a Clizia - Montale, Eugenio 1896-1981 (Mondadori, 2006)
Letters by E. Montale to Irma Brandeis (1905-1990), published for the first time; includes 2 letters by I. Brandeis.
Bound. - Texts in English or Italian. - Incl. 2 letters by I. Brandeis. - Cont. bibl. refs., notes, name index. - Letters by E. Montale to Irma Brandeis (1905-1990), publ. for the first time
Keywords: Brandeis, Irma -- Correspondence; Montale, Eugenio <1896-1981> -- Correspondence; Brandeis, Irma -- 1905-1990; Montale, Eugenio -- 1896-1981; Briefsammlung